Factors Affecting Decision Making to Engage in Sex Work among the Youth in the North East Thailand - รัชตาธนรัชต์ , ทัศนมินทร์; วงค์เจริญ, ณีรนุช (Journal of Health Science of Thailand, 2021)
TThe objectives of this study were to investigate the current situations, and factors affecting decisionmaking to be sex workers and to propose the solutions for preventing the youth sex work in the North East Thailand. The samples were divided into 3 groups: (1) 400 current and former youth sex workers, (2) 280 staff of the Center for the Protection of Children’s Rights Foundation, and (3) 14 policy makers relating to youth prostitution. Data collection instruments were questionnaire and semi-structure in-depth interview. The data were analyzed descriptive statistics, stepwise multiple regression analysis and content analysis. This research study revealed that personal factors and the needs had significant effect on the decision to become sex workers among the youth in the North East (p<0.05). The predictive power was at 97.3 and 59.8% (R2 =0.973 and 0.598) respectively. Sex work transactions through social media were at the highest level (Mean=4.58, SD=0.64). The solutions on this matter required the involvement of families, schools, communities and the society as a whole to promote positive reinforcement, close relationship, acknowledgement on the disadvantages of sex work, and increased educational and career opportunities. These would contribute positively toward the reduction of problems associated with sexwork in the youth.